A review of the flood hazard and risk management in the South Asian Region, particularly Pakistan - Shah, S.M.H. (Elsevier B.V., 2020)
Communities are being menaced by floods since ages. Flood occurrence not only imposes loss to the infrastructure and property but it also claims thousands of lives and leave millions homeless. Floods occur due to hydro-metrological and natural factors, however in recent years, human intervention has added new dimensions to it. South Asia's geography makes it susceptible to natural disasters and the most flood vulnerable regions in the world. In addition to this, countries in this region exhibit a high level of vulnerability unfortunately due to lack of resources, namely adaptive as well as coping capacities. Pakistan in particular, has a long history of floods. The country has witnessed almost 19 major flood events resulting into a cumulative flooding of over 594,700 km2 area with 166,075 villages affected and a total direct cumulative losses to the tune of about US 30 billion that ended up into the loss of 10,668 precious lives in the past 60 years. However, the floods of 2010 and 2011 were the most devastating. The national flood policy has been enhanced through several federal and provincial acts since the country came into existence. Unfortunately, there has not been reported any major reduction in the flood-to-damage ratio. Herein a brief review has been carried out that ponders on the current state of knowledge of the topic, particularly the nature of flood in the South Asian region, mainly Pakistan. Â© 2020